2020
DOI: 10.1002/jcp.29991
|View full text |Cite
|
Sign up to set email alerts
|

Towards analyzing the potential of exosomes to deliver microRNA therapeutics

Abstract: Exosome selectivity mechanisms underlying exosome-target cell interactions and the specific traits affecting their capability to communicate still remain unclear. Moreover, the capacity of exosomes to efficiently deliver their molecular cargos intracellularly needs precise investigation towards establishing functional exosomebased delivery platforms exploitable in the clinical practice. The current study focuses on: (a) exosome production from normal MRC-5 and Vero cells growing in culture, (b) physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…As shown in Fig 1 , the particles exhibited a hydrodynamic size of 132 ± 22 nm with a relatively large polydispersity index (PDI) of 0.39 ± 0.14 which corresponded to an average value from 10 repeated measurements. The DLS data showed a multimodal distribution indicating particle size heterogeneity with two major contributions, consistent with previously published DLS data [ 53 , 54 ]. According to the intensity parameter, particles with an average diameter of 39 nm (± 7 nm) accounted for about ~ 28% of the particle population ( Fig 1 , Peak 1), while larger particles that scatter light with greater intensity (150 nm ± 30 diameter) accounted for ~ 72% ( Fig 1 , Peak 2).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Fig 1 , the particles exhibited a hydrodynamic size of 132 ± 22 nm with a relatively large polydispersity index (PDI) of 0.39 ± 0.14 which corresponded to an average value from 10 repeated measurements. The DLS data showed a multimodal distribution indicating particle size heterogeneity with two major contributions, consistent with previously published DLS data [ 53 , 54 ]. According to the intensity parameter, particles with an average diameter of 39 nm (± 7 nm) accounted for about ~ 28% of the particle population ( Fig 1 , Peak 1), while larger particles that scatter light with greater intensity (150 nm ± 30 diameter) accounted for ~ 72% ( Fig 1 , Peak 2).…”
Section: Resultssupporting
confidence: 90%
“…The first is the size of the patient cohort, especially for high-risk MDS patients in RAEB-1 and RAEB-2 subgroups, which is due to the fact that MDS is a rare blood disorder. Second, blood samples were centrifuged at 4,000 × g whereas the recommended value by the manufacturer of the ExoQuick kit is 3,000 × g. This could affect the composition of the isolated EVs, however the DLS data are consistent ( S1 and S2 Files) with other work using a different isolation method (ultracentrifugation) [ 53 , 54 ]. Third, this work does not use pure isolated exosomes but exosome-rich fraction (ERF) as explicitly mentioned in the text.…”
Section: Resultsmentioning
confidence: 93%
“…To overcome these limitations the development of delivery platforms that allows maximum stability of the therapy and provide sufficient uptake capacity in target cells, while minimizing off-target side effects, is necessary. In this direction we previously employed exosomes derived from human MRC-5 cells and efficiently loaded them with siRNA/miRNA cargos [51]. Exosomes were efficient "bio-shuttles" by delivering miRNA molecules in a variety of cancer cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the balance between the electrostatic repulsion and space needs to be considered, which correlates to the volume used. To assess the influence of different incubation times, Giassafaki et al (2021) mixed siRNA with the MRC-5-and Vero-exosomes via stirring the mixture at 500 rpm for 90 min, 4 and 17 h at RT, and found that 90 min of incubation resulted the best for loading the exosomes with chemically synthesized oligonucleotides.…”
Section: Incubationmentioning
confidence: 99%